2019
DOI: 10.1136/rapm-2019-100673
|View full text |Cite
|
Sign up to set email alerts
|

Chloroprocaine versus prilocaine for spinal anesthesia in ambulatory knee arthroscopy: a double-blind randomized trial

Abstract: BackgroundIn ambulatory lower limb surgery, spinal anesthesia with rapid onset and a short duration of block is preferable. We hypothesized that the use of 2-chloroprocaine would be associated with a faster motor block recovery compared with prilocaine in knee arthroscopy. A difference of 15 min was considered clinically relevant.Methods150 patients were randomly allocated to receive intrathecally either 40 mg of 2-chloroprocaine or 40 mg of prilocaine. The primary outcome was the time to complete recovery fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…5 In recent years, chloroprocaine has been reintroduced into clinical practice and is widely used in emergency lower abdominal surgery and ambulatory lower limb surgery via epidural or spinal access. [6][7][8] Coppens et al reported that the onset of action was 2-3 min when the drug was administered epidurally for labor analgesia. 8 It has also been used for intrapartum emergency cesarean delivery in patients after labor EA with an onset time of 3-5 minutes, while that of lidocaine is 10-12 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, chloroprocaine has been reintroduced into clinical practice and is widely used in emergency lower abdominal surgery and ambulatory lower limb surgery via epidural or spinal access. [6][7][8] Coppens et al reported that the onset of action was 2-3 min when the drug was administered epidurally for labor analgesia. 8 It has also been used for intrapartum emergency cesarean delivery in patients after labor EA with an onset time of 3-5 minutes, while that of lidocaine is 10-12 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…The most common dose of chloroprocaine administered spinally was 50 mg (59.2%), then 40 mg (32.3%). We recently conducted a double-blind randomized trial comparing 40 mg chloroprocaine with 40 mg prilocaine for spinal anesthesia in ambulatory knee arthroscopy [2]. Using exactly the same discharge criteria, we found that the time from injection to eligibility for hospital discharge in the chloroprocaine arm (40 mg) in our study was substantial shorter, i.e., 222 ± 72 min (mean ± SD).…”
mentioning
confidence: 58%
“…Our previous study, in which we compared intrathecal prilocaine and 2-chloroprocaine 1% in ambulatory knee arthroscopy, inspired us to investigate the optimal dose of 2-chloroprocaine 1% for this indication. 2-Chloroprocaine 1% (40 mg) not only showed a faster offset of motor and sensory function than prilocaine (40 mg), it also had high peak levels suggesting a lower dose may further reduce an unnecessary prolonged length of stay 11…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, preservative-free 2-chloroprocaine 1% has regained interest as short acting spinal anesthetic for lower limb surgery lasting up to 60 min 2. Several double-blind randomized controlled studies have demonstrated that, compared with other local anesthetics, the short duration of block of 2-chloroprocaine 1% favors a fast hospital discharge in outpatient anesthesia 3–11. Our previous study, in which we compared intrathecal prilocaine and 2-chloroprocaine 1% in ambulatory knee arthroscopy, inspired us to investigate the optimal dose of 2-chloroprocaine 1% for this indication.…”
Section: Introductionmentioning
confidence: 99%